Analisis Pelaksanaan Pendidikan Inklusi ABK Autisme di SDN Sungai Andai 3 - Amaliah, Nahdiatun; Aripin, Salwa Salsabil Nur; Aminah, Siti; Suriansyah, Ahmad; Cinantya, Celia (Lumbung Pare Cendekia, 2025)
Penelitian berjudul